PENGEMBANGAN TES DIAGNOSTIK TWO-TIER MULTIPLE CHOICE BERBASIS HOTS MELALUI MEDIA KAHOOT PADA MATERI OPERASI BILANGAN BULAT KELAS IV SEKOLAH DASAR - Nuramna Fitriyani; Eka Sastrawati; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a Higher Order Thinking Skills (HOTS)-based two-tier multiple choice diagnostic test using Kahoot on integer operations for fourth-grade elementary school students. The background of this study was the limited availability of diagnostic assessment instruments that are able to identify students’ conceptual understanding and misconceptions in mathematics learning. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The developed product was a two-tier diagnostic test, in which the first tier measures students’ answer choices, while the second tier reveals the reasons behind their answers. Expert validation was conducted by material, media, and language experts to examine the feasibility and validity of the instrument. The field trial involved fourth- grade students to analyze the validity, reliability, level of difficulty, and discrimination index of the test items. The results indicated that the developed instrument was valid and reliable, with most items categorized as having moderate difficulty and good discrimination power. The use of Kahoot as a digital platform made the diagnostic assessment more interactive and increased students’ engagement during the learning process. Therefore, the HOTS-based two-tier diagnostic test developed in this study is suitable to be used as an alternative assessment instrument to identify students’ misconceptions and support meaningful mathematics learning in elementary schools.